2022
DOI: 10.3390/molecules27092783
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effect of Kidney Bean Resistant Starch on Hyperlipidemia—Induced Acute Pancreatitis and Related Intestinal Barrier Damage in Rats

Abstract: Accumulating attention has been focused on resistant starch (RS) due to its blood-lipid-lowering activities. However, reports on the potential bioactivities of RS for preventing hyperlipidemia acute pancreatitis (HLAP) are limited. Therefore, in this study, an acute pancreatitis model was set up by feeding a hyperlipidemia diet to rats, and subsequently evaluating the anti-HLAP effect of RS in kidney beans. The results show that the IL-6, IL-1β, and TNF-α of serum in each RS group were decreased by 18.67–50.00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…RS can strongly affect lipid metabolism by reducing many associated parameters (total cholesterol, triglycerides, LDL, HDL, VLDL and IDL) (Hernandez-Velazquez et al, 2020). Common bean effect on hypercholesterolemia may be due also to its RS concentration, as also partly found by various authors modulating the presence of the RS from bean in model rats (Tanaka et al, 2019;Kilua et al, 2020;Zuo et al, 2022). Loader et al (2021) found scarce effect of various dies containing variable bean RS concentration on the body weight, blood pressure, and aorta morphology, but found a reduction of the fasting total cholesterol or low-density lipoprotein cholesterol International Journal of Food Science and Technology 2023 depending on either the bean cooking strategies and presence of bean in the diet.…”
Section: Lipid Metabolism and Weight Control And Activity Of "Starch ...mentioning
confidence: 86%
See 1 more Smart Citation
“…RS can strongly affect lipid metabolism by reducing many associated parameters (total cholesterol, triglycerides, LDL, HDL, VLDL and IDL) (Hernandez-Velazquez et al, 2020). Common bean effect on hypercholesterolemia may be due also to its RS concentration, as also partly found by various authors modulating the presence of the RS from bean in model rats (Tanaka et al, 2019;Kilua et al, 2020;Zuo et al, 2022). Loader et al (2021) found scarce effect of various dies containing variable bean RS concentration on the body weight, blood pressure, and aorta morphology, but found a reduction of the fasting total cholesterol or low-density lipoprotein cholesterol International Journal of Food Science and Technology 2023 depending on either the bean cooking strategies and presence of bean in the diet.…”
Section: Lipid Metabolism and Weight Control And Activity Of "Starch ...mentioning
confidence: 86%
“…RS can strongly affect lipid metabolism by reducing many associated parameters (total cholesterol, triglycerides, LDL, HDL, VLDL and IDL) (Hernandez‐Velazquez et al ., 2020). Common bean effect on hypercholesterolemia may be due also to its RS concentration, as also partly found by various authors modulating the presence of the RS from bean in model rats (Tanaka et al ., 2019; Kilua et al ., 2020; Zuo et al ., 2022). Loader et al .…”
Section: Nutritional Health and Sensory Aspects Of Bean Rsmentioning
confidence: 99%